Design a capacitor bank using load flow analysis to improve power factor correction in the food industry - Malik, Mochamad Irlan; Adriansyah, Andi; Yanti, Yanti (Akademisi dan Saintis Indonesia (ASASI), 2024)
The impact of installing a capacitor bank on the performance of an electrical system is evaluated through the analysis of changes in active power, reactive power, voltage, and power factors at various buses. The analysis indicates that the addition of the capacitor bank results in a significant increase in active power and a substantial reduction in reactive power. At Bus 1 (20 kV), active power increased from 648.93 kW to 687.38 kW, while reactive power decreased from 613.19 kVAR to 124.24 kVAR. At Bus 2 (0.4 kV), active power from 635.65 kW to 679.25 kW, and reactive power dropped from 560.59 kVAR to 92.046 kVAR. Voltage levels remained stable or slightly increased, and the power factor showed significant improvement, rising from 72.684% to 98.046% on Bus 1 and from 75.000% to 99.094% at Bus 2. Overall, the capacitor bank enhances system efficiency by optimizing power usage and reducing reactive power.